My Therapist: A Cognitive Approach towards Natural Language Processing - Ms.Briskilal.J, Ashwin Singh, Divyanshu Ojha (International Journal of Advanced Science and Technology, 2020)
Talk therapy (which is also known as psychotherapy) is an important and growing field to a range of treatment for depression, bipolar disorder or other mood disorders. A good therapist can help a person to cope with his or her feelings and thought patterns and adapt to their sentiments by problem solving and changing behavior patterns that may contribute to the cognitive distortions or the disorder’s symptoms.While Conversational AI is the study of techniques and strategies for software agents that can engage in natural conversational interactions with humans. As of late, many conversational interfaces/assistants such as Amazon Alexa, Google Assistant, Apple’s Siri, J.A.R.V.I.S and others have become a focal point in both academic and industrial research because of their rapid market uptake and rapidly increasing range and scope of capabilities. The first generation of these Conversational assistants have been focused on short errand situated discourse as opposed to longer freestyle discussions and task-oriented dialog rather than longer free-form conversations that occur naturally in social, emotional and professional human interaction using human language. Achieving sustained, coherent, intelligible and engaging dialog are the next frontiers for conversational AI. Adding to these features of a conversational AI using NLP, introduction of a conversational therapeutic assistant which will help in these various procedures of psychotherapy and treatment of these mental disorders using Cognitive behavioral therapy(CBT) which is a short-term therapy technique approach that can help people find new ways to induce behavioral changes by changing their thought patterns.Keywords: Cognitive Behavioral Therapy(CBT); Natural Language Processing(NLP); Conversational Artificial Intelligence(AI).